Why the Implementation of the Clean-Up (Saberpungli) Policy for Illegal Levies has not yet Reached the Target in East Java - Zakariya Zakariya; Teguh Santoso; Samsul Arifin; Taufillah Ifada; May Yusita Sari (Iapa Proceedings Conference, 2019)
Since the issuance of Presidential Regulation No. 87 of 2016 concerning the task force to clean up illegal levies (Saberpungli), as a manifestation of Jokowi's commitment to the nine ideals (nawacita) that have been scheduled by the Jokowi government, especially related to the goal of strengthening the country's presence in conducting corruption-free, dignified and reliable system reform and law enforcement has been followed up by the provincial government. The province of East Java is no exception. The East Java government has made a Sweep-Off Task Force for Illegal Levies with the issuance of the Governor's policy No. 188/624 / KTPS / 013/2016. The implementation of the Governor's regulation has not been effective and efficient because the capture operation in its implementation only targets illegal levies valued at Rp. 10.00 - Rp. 100,000, while the legal process in each case costs between Rp. 50,000,000 to Rp. 100,000, - In addition, when a suspect acts to serve public activities, public service activities are hampered. For example educators, paramedics and others. The research question is Why The Implementation of the clean-up policy for illegal levies has not yet reached the target in East Java? This study uses a qualitative method approach by exploring information from key informants involved in implementing Saberpungli's policies, namely from the inspectorate, prosecutor's office and police as the main data and related documents. The results of the study show that the implementation of the clean-up policy in East Java was not able to reach the target due to five factors. First, coordination between task forces is still weak. Second, the lack of support from the regional government budget in other levies. Third, there is no SOP that the implementing agency can agree on and understand. As for recommendations that the implementation of the clean-up policy of illegal levies can reach the target, it is necessary to demonstrate the commitment of the provincial government by budgeting appropriately and need to increase coordination with the SOP as a shared direction in eradicating the practice of illegal collection in the public sector.